Enhancing Teacher Performance through Participatory Supervision in Indonesian Islamic Schools - Dodo Murtado; Cecep Soleh Kurniawan (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
Improving the quality of education in Indonesia requires a more participatory and value-based supervision approach, particularly in Islamic schools. This study aims to examine the implementation of participatory supervision at MAN 2 Tasikmalaya and to analyze its impact on teacher performance through theological and educational management perspectives. Employing a qualitative case study design, data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that participatory supervision, when integrated with Islamic theological values such as musyawarah (deliberation), amanah (trustworthiness), and ihsan (excellence), enhances teacher involvement in the learning process and improves teaching quality. In addition, this supervision model strengthens collaborative relationships between principals and teachers, fostering responsiveness to feedback and increasing professional motivation. The study concludes that value-based participatory supervision is effective in improving teacher performance in Islamic schools. Its implications highlight the need for supervision models that prioritize not only cognitive aspects of education but also the development of character and morality, thereby supporting the broader goals of Islamic education